UJI EFEKTIVITAS WEBSITE INTERAKTIF BERBASIS PBL TERHADAP LITERASI DIGITAL MURID SEKOLAH DASAR - Heru Windarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the effectiveness of an interactive website based on Problem-Based Learning (PBL) in enhancing the digital literacy skills of primary school pupils. Aligned with recent educational transformation policies that emphasize pupils as active subjects, this research serves as a follow-up study to strengthen empirical evidence regarding digital media utilization in basic education. The research employed a quantitative method with a quasi-experimental design, specifically a one-group pretest-posttest design. The sample consisted of 27 pupils from class VB at UPT SD Negeri Manjung. Data were collected through written tests developed based on digital literacy indicators and analyzed using normality tests and paired sample t-tests via SPSS 25 software. The improvement effectiveness was measured using the normalized N-Gain analysis. The results indicate that: (1) there is a significant effect of using the PBL-based website on pupils' digital literacy skills, evidenced by a Sig. (2-tailed) value of 0.000 < 0.05; (2) the average N-Gain score achieved was 0.56, which falls into the